The Latitudinal Variability of Oceanic Rainfall Properties and Its Implication for Satellite Retrievals: 1. Drop Size Distribution Properties. Issue 23 (14th December 2019) - Protat, Alain; Klepp, Christian; Louf, Valentin; Petersen, Walter A.; Alexander, Simon P.; Barros, Ana; Leinonen, Jussi; Mace, Gerald G.
Abstract: In this study, we analyze an in situ shipboard global ocean drop size distribution (DSD) 8‐year database to understand the underpinning microphysical reasons for discrepancies between satellite oceanic rainfall products at high latitudes reported in the literature. The natural, latitudinal, and convective‐stratiform variability of the DSD is found to be large, with a substantially lower drop concentration with diameter smaller than 3 mm in the Southern hemisphere high latitude (S‐highlat, south of 45°S) and Northern Hemisphere polar latitude (N‐polar, north of 67.5°S) bands, which is where satellite rainfall products most disagree. In contrast, the latitudinal variability of the normalized oceanic DSD is small, implying that the functional form of the normalized DSD can be assumed constant and accurately parameterized using proposed fits. The S‐highlat and N‐polar latitude bands stand out as regions with oceanic rainfall properties different from other latitudes, highlighting fundamental differences in rainfall processes at different latitudes and associated specific challenges for satellite rainfall retrieval techniques. The most salient differences in DSD properties between these two regions and the other latitude bands are: (1) a systematically higher (lower) frequency of occurrence of rainfall rates below (above) 1 mm h ‐1, (2) much lower drop concentrations, (3) very different values of the DSD shape parameter ( μ 0 ) from what is currently assumed in satellite radar rainfall algorithms, and (4) very different DSD properties in both the convective and stratiform rainfall regimes. Overall, this study provides insights into how DSD assumptions in satellite radar rainfall retrieval techniques could be refined. Key Points: The latitudinal variability of statistical oceanic rainfall properties is characterized for the first time Results should inform improvements to the GPM radar rainfall retrievals